Developing Flipped Classroom Learning Materials to Improve Mathematical Literacy and Learning Independence - Nasution, Dinda Indriani; Dewi, Izwita; Syahputra, Hermawan (Jurnal Perspektif, 2025)
This study aims to create a high-quality Flipped Classroom Model-based learning device to improve mathematical literacy and learning independence of seventh grade junior high school students on data centralization measurement material. This research method is a development research of the Analysis, Design, Development, Implementation, Evaluation (ADDIE) method. The results of this study are that the Flipped Classroom Model-based learning device is valid and practical; students' mathematical literacy skills increased by 0.65 which is classified as moderate; students' independent learning abilities increased by 0.23 which is classified as moderate. The Flipped Classroom Model is effective for learning Data Centralization Measurement. The Flipped Classroom Model functions well for learning data centralization measurements. More than 75% of learning objectives were achieved, more than 85% of students scored at least 75, more than 85% of students responded positively to the flipped classroom model-based learning device, and the use of time on the learning device did not exceed regular learning hours.